STRATEGI PENGEMBANGAN WISATA SYARIAH DI KAMPUNG NAGA DAN KAMPUNG DUKUH PROVINSI JAWA BARAT - Misno Mohammad Djahri (Institut Agama Islam Sahid Bogor, 2020)
Sharia Tourism is a term used by the Ministry of Tourism and Creative Economy of the Republic of Indonesia for tourism programs based on Islamic Sharia values. This program was launched in mid December 2012 as the implementation of Law no. 10 of 2009 concerning Tourism. West Java as a sharia tourist destination has the potential for tourism objects that can be developed according to Islamic sharia values, namely Kampung Dukuh and Kampung Naga. The tourism potential that exists at these two locations is in the form of natural tourism, local traditions, pilgrimage tours and historical tours.This study formulates a strategy for developing sharia-based tourism in Kampung Dukuh and Kampung Naga. The aim is to identify the potential of sharia tourism in Kampung Dukuh and Kampung Naga, analyze the internal and external environment and determine the development strategy of the two traditional villages as sharia tourist attractions. The data in this study were obtained through participatory observation methods, interviews and documentation.The results show that the strength of sharia tourism in Kampung Dukuh and Kampung Naga includes community religious values ​​and rituals, pilgrimage tourism objects, unique architecture, natural beauty of the mountains, good road access (Kampung Naga). Meanwhile, the weaknesses of Kampung Dukuh and Kampung Naga include the lack of transportation availability (Kampung Dukuh), lack of tourism facilities, lack of available parking space (Kampung Dukuh), lack of toilet facilities, not maximal promotion, and unavailability of Tourist Information Center (Kampung Dukuh). Based on the analysis of strengths and weaknesses, four development strategies that can be applied are formulated, namely product development strategies, promotion development strategies, sustainable tourism strategies and Human Resources (HR) development strategies based on Islamic Sharia values.